Identical Penicillin-Binding Domains in Penicillin-Binding Proteins of Streptococcus pneumoniae Clinical Isolates with Different Levels of β-Lactam Resistance - Chesnel, Laurent (American Society for Microbiology, 2005)
We have sequenced the penicillin-binding domains of the complete repertoire of penicillin-binding proteins and MurM from 22 clinical isolates of Streptococcus pneumoniae that span a wide range of β-lactam resistance levels. Evidence of mosaicism was found in the genes encoding PBP 1a, PBP 2b, PBP 2x, MurM, and, possibly, PBP 2a. Five isolates were found to have identical PBP and MurM sequences, even though the MICs for penicillin G ranged from 0.25 to 2.0 mg/liter. When the sequences encoding PBP 1a, PBP 2b, and PBP 2x from one of these isolates were used to transform laboratory strain R6, the resulting strain had a resistance level higher than that of the less resistant isolates carrying that PBP set but lower than that of the most resistant isolates carrying that PBP set. This result demonstrates that if the R6 strain is arbitrarily defined as the standard genotype, some wild genetic backgrounds can either increase or decrease the PBP-based resistance phenotype.